2014
DOI: 10.1128/jvi.01321-14
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus (NDV) Recombinants Expressing Infectious Laryngotracheitis Virus (ILTV) Glycoproteins gB and gD Protect Chickens against ILTV and NDV Challenges

Abstract: Infectious laryngotracheitis (ILT) is a highly contagious acute respiratory disease of chickens caused by infectious laryngotracheitis virus (ILTV). IMPORTANCEThis paper describes the development and evaluation of novel bivalent vaccines against chicken infectious laryngotracheitis (ILT) and Newcastle disease (ND), two of the most economically important infectious diseases of poultry. The current commercial ILT vaccines are either not safe or less effective. Therefore, there is a pressing need to develop safer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 43 publications
0
59
0
Order By: Relevance
“…Additionally, an NDV-vectored influenza virus vaccine can function as a bivalent vaccine against both influenza virus and NDV infections in chickens (10). This conclusion is based on the HI antibody titers against NDV in both NDV-H5-and NDV-H7-vaccinated groups (Table 2), since both vaccines elicited good immune responses against NDV in oculonasally and intramuscularly vaccinated chickens, with HI titers ranging from 1:40 to 1:320 after booster; these HI titers should be able to provide protection against NDV infection based on previous observations (29). In the field, although the seropositive prevalence of NDV in chickens is high, based on our data describing specific HI titers against NDV (Table 2), an anamnestic booster response was found in chickens which had HI titers of 1:10 to 1:40 against NDV after the first vaccination.…”
mentioning
confidence: 80%
“…Additionally, an NDV-vectored influenza virus vaccine can function as a bivalent vaccine against both influenza virus and NDV infections in chickens (10). This conclusion is based on the HI antibody titers against NDV in both NDV-H5-and NDV-H7-vaccinated groups (Table 2), since both vaccines elicited good immune responses against NDV in oculonasally and intramuscularly vaccinated chickens, with HI titers ranging from 1:40 to 1:320 after booster; these HI titers should be able to provide protection against NDV infection based on previous observations (29). In the field, although the seropositive prevalence of NDV in chickens is high, based on our data describing specific HI titers against NDV (Table 2), an anamnestic booster response was found in chickens which had HI titers of 1:10 to 1:40 against NDV after the first vaccination.…”
mentioning
confidence: 80%
“…The foreign genes are usually inserted into a non-coding region at different intergenic regions of the NDV genome, and evaluation of these vaccine candidates in clinical trials revealed different levels of protection against targeted pathogen challenge (Bukreyev et al, 2005;DiNapoli et al, 2007;Hu et al, 2011;Huang et al, 2004;Park et al, 2006;Yu et al, 2013;Zhao et al, 2014). Although the immune response to vaccination is influenced by many factors, the expression level of foreign genes is undoubtedly the most important one.…”
mentioning
confidence: 99%
“…A full-length cDNA clone (FLC), pFLC-VG/GA, encoding the complete antisense genome of the NDV VG/GA strain was generated through three steps of cloning using an InFusion PCR Cloning kit (Clontech) and a similar cloning approach as described previously (Hu et al, 2011;Zhao et al, 2014). The GFP gene ORF together with the NDV transcriptional signals derived from the P-M gene junction region was successfully amplified, and inserted into the NP/ P, P/M, M/F, F/HN or HN/L non-coding region in the VG/GA FLC respectively, resulting in five VG/GA-GFP recombinant cDNA clones (Fig.…”
mentioning
confidence: 99%
“…A number of foreign antigens derived from avian viral pathogens, such as the haemagglutinin (HA) gene of avian influenza virus, the VP2 gene of infectious bursal disease virus, the S2 gene of infectious bronchitis virus, the glycoprotein B (gB) and D (gD) of infectious laryngotracheitis virus, and the glycoprotein (G) gene of avian metapneumovirus (DiNapoli et al, 2010;Hu et al, 2011;Huang et al, 2004;Toro et al, 2014;Zhao et al, 2014), have been expressed by NDV as bivalent vaccines against NDV and the target avian pathogen challenges. However, most of the NDV vaccine vector strains are thermolabile and may not be suitable for use as vaccine vectors for village chickens.…”
Section: Introductionmentioning
confidence: 99%